Nutrients And Heavy Metals In Vegetables Produced Organically And Conventionally - Heng, Huey Chyi (Universiti Malaysia Sarawak (UNIMAS), 2011)
Heavy metals nitrate and phosphorus of four types of vegetables namely Choy Sum, Kiew Choy, Bok Choy and Baby Bok Choy from an organic vegetable farm at Siburan and two conventional farms at Tapah and Beratok were investigated. The heavy metals included Fe, Zn, Cu, Cd, Pb and Cr. The findings showed that Fe and Zn had the highest concentrations in all the vegetable samples in the three farms. This was followed by Cu, Cr, Cd and Pb. Most of the organic vegetables were found to contain the highest iron and nitrate concentrations and the lowest concentrations in zinc and chromium compared to the two conventionally produced vegetables. Fe concentration range in organic vegetable was 113.5 mglkg to 207.0 mglkg. In conventional vegetables, Fe concentration range was 53.5 mg/kg to 133.0 mg/kg. Correlation test showed that organic vegetables nitrate concentrations were strongly correlated with the concentration in their respective soil samples (n=12, r = 0.809, p=0.001). Cu, Cr and phosphorus also showed correlation between vegetables and their respective soil (n=12, R2=0.762, p=0.002; n=12, R2=0.603, p=0.014; n=12, R2=0.818, p=O.OOl). It was safe to consume the vegetables where all the analyzed elements were below the maximum permitted limit.